2018
DOI: 10.3390/ijms19020372
|View full text |Cite
|
Sign up to set email alerts
|

Poly-N-Acetyllactosamine Neo-Glycoproteins as Nanomolar Ligands of Human Galectin-3: Binding Kinetics and Modeling

Abstract: Galectin-3 (Gal-3) is recognized as a prognostic marker in several cancer types. Its involvement in tumor development and proliferation makes this lectin a promising target for early cancer diagnosis and anti-cancer therapies. Gal-3 recognizes poly-N-acetyllactosamine (LacNAc)-based carbohydrate motifs of glycoproteins and glycolipids with a high specificity for internal LacNAc epitopes. This study analyzes the mode and kinetics of binding of Gal-3 to a series of multivalent neo-glycoproteins presenting comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(93 citation statements)
references
References 56 publications
(107 reference statements)
8
85
0
Order By: Relevance
“…ELISA‐type inhibition studies were performed according to an already established protocol by Elling and co‐workers. [ 30 ] Inhibition of Gal‐1 and Gal‐3 binding to asialofetuin was investigated for glycoligands 1b – 13b (and 8a for Gal‐1) with final concentrations between 0.1 × 10 −6 and 2000 × 10 −6 m using phosphate buffered saline (PBS) buffer (150 × 10 −3 m NaCl, 50 × 10 −3 m NaH 2 PO 4 , pH 7.5). All measurements were performed two times in triplicates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ELISA‐type inhibition studies were performed according to an already established protocol by Elling and co‐workers. [ 30 ] Inhibition of Gal‐1 and Gal‐3 binding to asialofetuin was investigated for glycoligands 1b – 13b (and 8a for Gal‐1) with final concentrations between 0.1 × 10 −6 and 2000 × 10 −6 m using phosphate buffered saline (PBS) buffer (150 × 10 −3 m NaCl, 50 × 10 −3 m NaH 2 PO 4 , pH 7.5). All measurements were performed two times in triplicates.…”
Section: Methodsmentioning
confidence: 99%
“…[ 2,8–17 ] In cases where galectin‐3 has been shown to be responsible for tumor metastasis and migration, several groups have endeavored to design compounds to inhibit them. One group of examples involves the multivalent presentation of carbohydrate residues on macromolecular scaffolds as described by Gabius et al., [ 18,19 ] Roy et al., [ 20,21 ] Nilsson et al., [ 22,23 ] Wang et al., [ 24 ] Argueso et al., [ 25 ] Cloninger et al., [ 26,27 ] Lecommandoux et al., [ 28 ] Elling and co‐workers, [ 29–31 ] Percec et al., [ 32–35 ] Putnam et al., [ 36 ] and more recently Rosencrantz et al. [ 37 ] This approach takes advantage of the ability of galectin‐3 to oligomerize in the presence of multivalent ligands leading to an effective increase in binding avidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the angular shift caused by the traditional SPR (MOA-based) chip was similar at flow rates of 30 and 60 µL/min. We performed a 1:1 interaction of the SPR biosensor sensing surface with anti-CYFRA21-1 protein using the binding Langmuir model (Bumba et al, 2018). The kinetic analysis for the traditional SPR chip at a flow rate of 60 µL/min yielded an affinity binding constant (K A ) of 1.78 × 10 8 M −1 , association rate constant (k a ) of 2.71 × 10 4 M −1 S −1 and dissociation rate constant (k d ) of 15.23 × 10 −5 S −1 .…”
Section: Kinetic Analysis Of Binding Interaction Between Carboxyl-mosmentioning
confidence: 99%
“…Previous studies have indicated that galectin-3 exhibits only weak affinity to O-glycoproteins and O-glycopeptides expressing single core 1 O-glycans (Galb1-3GalNAc or NeuAcα2-3Galb1-3GalNAc) 34,42 . Instead, internal LacNAc glycans on extended oligosaccharides have been described to be the high affinity ligands for galectin-3 43 . Here, we suggest that interaction between galectin-3 and native lubricin is mediated by short single LacNAc extended core 2 structures.…”
Section: Truncation Of Sf Lubricin O-glycosylation In Oa and Galectin-3mentioning
confidence: 99%